Vortices in a mesoscopic superconducting disk of variable thickness - Sardella, Edson [UNESP]; Brandt, E. H. (Iop Publishing Ltd, 2010)
In this paper we study the formation of vortices in a mesoscopic superconducting disk of thickness equal to or of the same order as the coherence length xi(T). The roughness of the lower and upper surfaces of the disk is taken into account. We also compute the total induced current and the magnetization for the disk in the presence of an external applied magnetic field.